CHINESE IMPORTS UNDER-INVOICED FROM THE PERSPECTIVE OF THE TAXMAN - Singh, Anand Kumar; Pradeep, (The journal of contemporary issues in business and government, 2022)
This study focuses on the harm that inappropriate trade invoice utilisation does to the growth of the economy. Due to the fact that China is the primary trading partner, trade figures with China are emphasised, empirically validated, and exhibited. The findings of the study demonstrate that China is engaging in illicit trade practises, which is affecting India's economy. The research revealed that excessive and inadequate invoicing is a major cause of capital flight. Long-term global economic downturn prompts some economists and policymakers to demand for stricter regulations to safeguard their domestic economies. If put into practise, this might cause a high tariff and non-tariff system similar to the one that governed the pre-globalized world economy. Mismatched trade statistics between developed and developing nations point to significant misreporting of economic data, mostly by traders in developing nations. Due torigid exchange rate regimes, severe import limitations and export subsidies prevailing in less developed nations. This study specifically addresses the under-invoicing of imports as a result of high trade restrictions in a market where domestic companies compete with importers. The studyanalyses that how the levels of under-invoicing isimpacted by tariff levels, market structure, and government involvement (in the form of the extent of monitoring and the severity of sanctions).The information collected and reported from China and India showed a considerable discrepancy, and Indian tax authorities are now thoroughly investigating the issue to look for any instances of under-invoicing of Chinese business imports. A detailed review revealed that the country's invoiced imports were far less than China's exports to India.